Jamur Pelarut Fosfat untuk Menekan Penyakit Moler (Fusarium oxysporum F. SP. Cepae) dan Meningkatkan Pertumbuhan Bawang Merah - Hadiwiyono Hadiwiyono; Sudadi Sudadi; Claudia Sandy Sofani (Faculty of Agriculture, Universitas Sebelas Maret, 2014)
Title : P-solubilizing Fungi as Biological Control Agents to Increase Growth and Prevent Moler Disease of Red Onion. This research aim to obtain phosphate-solubilizing fungi have antagonistic ability to Fusarium oxysporum f. cepae, and increase soil available-P. The experiment was hold in April 2013 to February 2014. Antagonistic capability was observed in two stages i.e. in vitro test which was conducted in the Laboratory of Soil Biology and Biotechnology, while in vivo test in green house, Faculty of Agriculture, Sebelas Maret University Surakarta. The experimental design used was completely randomized design (CRD). The treatment factors of in vitro test were kinds of phosphate solubilizing fungi and incubation time with Pikovkaya liquid medium, while the treatment factor of in vivo test was isolates combination of phosphate solubilizing fungi. Each treatment combination was repilcate three times. The observated variable included soil available phosphate, shallot height, shoot dry weight, moler disease intensity, infection rate, and area under the disease progress curve. The research obtained 3 isolates of fungi with high potential as inoculums of P-solubilizing biofertilizer and biological control agents against moler desease of red onion. The resullt showed that mix of JK12 isolate (isolated from Entisol of Bantul District) and isolate of JK14 (from Andisol of Tawangmangu sub district) demonstrated the highest ability in solubilizing phosphate and suppressing moler disease of red onion.